TLR21's agonists in combination with Aeromonas antigens synergistically up-regulate functional TLR21 and cytokine gene expression in yellowtail leucocytes. (August 2016) - Reyes-Becerril, Martha; Ascencio-Valle, Felipe; Hirono, Ikuo; Kondo, Hidehiro; Jirapongpairoj, Walissara; Esteban, Maria Angeles; Alamillo, Erika; Angulo, Carlos
Abstract: The purpose of this study was to characterize the TLR21 gene from yellowtail ( Seriola lalandi ) and its functional activity using TLR agonist stimulation and Aeromonas antigens. The TLR21 nucleotide sequence from yellowtail was obtained using the whole-genome shotgun sequencing method and bioinformatics tools. Basal TLR21 gene expression was analyzed in several tissues. Subsequently, the gene expression of TLR21 and cytokines IL-1β and TNF-α was evaluated in TLR agonist (CpG-ODN2006, LPS, and Poly I:C) exposing head kidney leucocytes, which were then subjected to Aeromonas antigen stimulation. The yellowtail full-length cDNA sequence of Sl TLR21 was 3615 bp (980 aa) showing a high degree of similarity with the counterparts of other fish species and sharing the common structural architecture of the TLR family, including LRR domains, one C-terminal LRR region, and a TIR domain. Gene expression studies revealed the constitutive expression of TLR21 mRNA in all the analyzed tissues; the highest levels were observed in spleen and head kidney where they play an important role in the fish immune system. Transcripts of TLR21 and the downstream IL-1β and TNF-α cytokine genes were most strongly up-regulated after exposure to the TLR agonists following Aeromonas antigen stimulation, suggesting they are involved in immune response. The results indicated that TLR agonists, in combination with Aeromonas antigens in head kidney leucocytes, synergistically enhance TLR21 and cytokines in yellowtail. Highlights: TLR21gene was identified and characterized in Seriola lalandi. TLR21 was up-regulated after TLR agonists plus Aeromonas antigens stimulation. Both IL-1β and TNF-α were strongly enhanced after TLR agonists and Aeromonas antigens stimulation.